Preparation, Characterization, and Application of Novel Ferric Oxide-Amine Material for Removal of Nitrate and Phosphate in Water - Trung Thanh Nguyen; Tri Thich Le; Phuoc Toan Phan; Nhat Huy Nguyen (Journal of Chemistry)
Ferric oxide-amine material was synthesized and applied as a novel adsorbent for nitrate and phosphate removal from aqueous solution. The properties of ferric oxide-amine were examined using TGA, FTIR, BET, SEM, EDX, SEM-mapping, and XRD analysis. The results showed that the adsorption using ferric oxide-amine material reached equilibrium after 30 and 60 min for nitrate and phosphate, respectively. The highest nitrate and phosphate adsorption capacities were 131.4 mg nitrate/g at pH 5-6 and 42.1 mg phosphate/g at pH 6. The effects of adsorbent dosage, initial concentrations of nitrate and phosphate, and adsorption temperature were also investigated. Among the three adsorbents of ferric oxide-amine, ferric oxide, and Akualite A420 ion exchange resin, ferric oxide-amine material had the highest adsorption capacity for nitrate and phosphate removal. These results suggest a great potential use of ferric oxide-amine material for water treatment in practical applications.